Corneal endothelium self‐healing mathematical model after inadvertent descemetorhexis. Issue 10 (October 2015) - Jullienne, Rémy; Manoli, Pierre; Tiffet, Théophile; He, Zhiguo; Rannou, Klervi; Thuret, Gilles; Gain, Philippe
Abstract : N/A: An 85‐year‐old man presented with an unusual complication of cataract surgery. During injection of an ophthalmic viscosurgical device, Descemet membrane was accidentally dissected and removed during the capsulorhexis. Early postoperative visual acuity was counting fingers as a result of massive corneal edema. Using a mathematical model of the endothelium, we evaluated the corneal endothelial cell self‐healing capacity from the periphery by calculating the theoretical endothelial cell density (ECD) after corneal endothelial cell redistribution. The calculated theoretical ECD was 1592 cells/mm 2 . At 22 months, the corrected distance visual acuity improved to 20/25. The central ECD was 549 cells/mm 2, 516 cells/mm 2, 987 cells/mm 2, and 1344 cells/mm 2 at 5, 8, 16, and 22 months, respectively. The originality of this case is based on the mathematical simulation of the corneal endothelial cell's spontaneous self‐healing process, deferring keratoplasty. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.